Successful Percutaneous Coronary Interventionin a Patient with Dextrocardia and Situs Inversus-a case report - Ahsan, Syed Ali; Rahman, Hafizur; Hossain, Ahmed Shafiqul; Siddique, Md Abu; Mahmood, Manzoor (University Heart Journal, 2013)
Dextrocardia is a rare congenital anomaly of development characterized by a mirror- image position of the heart. Unlike dextrocardia with situs solitus or ambiguus, the coincidence of congenital heart disease is relatively low among dextrocardic patients with situs inversus. However, patients with dextrocardia may suffer from coronary heart disease as do people with normally positioned hearts. Few cases of coronary angiography and percutaneous coronary intervention in patients with dextrocardia have been reported. This is a case of a 48-year-old male patient with dextrocardia who developed unstable angina and was able to undergo diagnostic catheterization and percutaneous coronary intervention. We successfully performed percutaneous coronary angioplasty followed by coronary stenting to the left circumflex artery (LCX) and described our experience in the selection of the guiding catheters (standard preformed catheters), angiographic image acquisition (mirror image views with subtle modification) and coronary catheter engaging techniques (opposite-direction catheter rotations). DOI: http://dx.doi.org/10.3329/uhj.v8i2.16089 University Heart Journal Vol. 8, No. 2, July 2012